Why do parties support emigrant voting rights?. Issue 3 (23rd September 2019) - Østergaard-Nielsen, Eva; Ciornei, Irina; Lafleur, Jean-Michel
Abstract: Policies allowing enfranchisement of non-resident citizens (emigrants and their descendants) are now implemented in the majority of states worldwide. A growing number of case studies show that the extension of voting rights to non-resident citizens is often contested among country of origin political parties. However, there is no systematic comparative study of why different political parties support or oppose external voting rights and how this position is framed by the parties. Drawing on a unique data set based on 34 debates across 13 countries, we estimate the extent to which ideology and party family are correlated with the positioning and framing of parties. Among the findings are that the more to the right is a party, the more it tends to support external voting rights, except in the case of radical right parties. The position on emigrant voting rights is largely framed along more pragmatic arguments.